2020
DOI: 10.21203/rs.3.rs-43736/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel FN-MdV Pathway and Its Role in Cerebellar Multimodular Control of Sensorimotor Behavior

Abstract: The cerebellum is crucial for various associative sensorimotor behaviors. Delay eyeblink conditioning (DEC) depends on the simplex lobule-interposed nucleus (IN) pathway, yet it is unclear how other cerebellar modules cooperate during this task. Here, we demonstrate the contribution of the vermis-fastigial nucleus (FN) pathway in controlling DEC. We found that task-related modulations in vermal Purkinje cells and FN neurons predict conditioned responses (CRs). Coactivation of the FN and the IN allows for the g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
2
2
0
Order By: Relevance
“…The data on suppression PCs in the medial cerebellum showing a relatively late SS modulation during execution of both pro-and antisaccades as well as those on facilitation PCs in the lateral cerebellum showing a prominent modulation at the end of the instruction of antisaccades indicate that different modules of different cerebellar regions can simultaneously contribute to the same complex behavior, yet with different particularities. A similar conclusion was drawn from a recent study on delay eyeblink conditioning 70 . Even though this form of conditioning is classically considered to be controlled solely by modules in lobule simplex of the lateral cerebellum[Citation error], Wang and colleagues have shown that modules of the medial cerebellum are equally essential, yet also contributing in a slightly differential fashion, possibly regulating mainly muscle tone 70 .…”
Section: Cerebellar Modules Operate In Parallelsupporting
confidence: 87%
See 2 more Smart Citations
“…The data on suppression PCs in the medial cerebellum showing a relatively late SS modulation during execution of both pro-and antisaccades as well as those on facilitation PCs in the lateral cerebellum showing a prominent modulation at the end of the instruction of antisaccades indicate that different modules of different cerebellar regions can simultaneously contribute to the same complex behavior, yet with different particularities. A similar conclusion was drawn from a recent study on delay eyeblink conditioning 70 . Even though this form of conditioning is classically considered to be controlled solely by modules in lobule simplex of the lateral cerebellum[Citation error], Wang and colleagues have shown that modules of the medial cerebellum are equally essential, yet also contributing in a slightly differential fashion, possibly regulating mainly muscle tone 70 .…”
Section: Cerebellar Modules Operate In Parallelsupporting
confidence: 87%
“…A similar conclusion was drawn from a recent study on delay eyeblink conditioning 70 . Even though this form of conditioning is classically considered to be controlled solely by modules in lobule simplex of the lateral cerebellum[Citation error], Wang and colleagues have shown that modules of the medial cerebellum are equally essential, yet also contributing in a slightly differential fashion, possibly regulating mainly muscle tone 70 . Interestingly, similar to the current pro-and antisaccade tasks, during eyeblink conditioning the medial and lateral cerebellum also both engage facilitation and suppression cells, and they also operate at relatively low and high baseline firing frequencies, respectively 37,70 .…”
Section: Cerebellar Modules Operate In Parallelsupporting
confidence: 87%
See 1 more Smart Citation
“…For example, PC activity in the lobule simplex of rhesus monkeys correlates strongly with the velocity of horizontal eye movements (Marple-Horvat & Stein, 1990). Likewise, PCs in the lobule simplex of mice play a role in delay eyeblink conditioning (Heiney, Wohl et al, 2014;ten Brinke et al, 2015;Wang et al, 2020), while those in rabbits have been shown to contribute to conditioning of the nictitating membrane response (Schreurs et al, 1991). The current findings on a potential role of PCs in the murine lobule simplex in controlling kinematics of whisker movements are in line with the observations by Sharp & Gonzalez (1985), who showed that stimulation of the whiskers in rats alters activity in the lobule simplex.…”
Section: Motor Control By the Paramedian Lobule And Lobule Simplexmentioning
confidence: 99%